The folly and the glory : America, Russia, and political warfare, 1945-2020 - Weiner, Tim (Henry Holt and Company, 2020)
"With vivid storytelling and access to insider accounts, Weiner sets out to trace the roots of Russian-American political warfare--conflict waged without weapons--over the last seven decades to understand how a president landed in the White House with the help of an expansive, covert Russian campaign. Russia's modern revival of Soviet-era intelligence operations constitutes one of the most significant threats to democracy in the United States and around the world, and yet the US has not engaged its own political warfare methods in defense, even as our own justice department has concluded unequivocally that Russia influenced the 2016 election. To get to the heart of what's at stake and find potential solutions, Weiner examines long-running twentieth century CIA operations, political machinations by the Soviet KGB around the world, the erosion of American political warfare after the Cold War, and why twenty-first century Russia has returned to the practice while the US has not. Weiner takes us behind closed doors and into the deliberation rooms of past and present Russian and American intelligence operations that directly led to-and help illuminate-the current administration and the future of American democracy"--